Transgastric jejunostomy - Ventura, Gustavo; Praderi, Raúl (Cirugía del Uruguay, 1979)
In 1973 we published our technique for transgastric jejunostomy which we had been using since 1971. This procedure consists in performing a minimun gastrojejunostomy in the posterior face of stomach, through which is placed a jejunal catheter for feeding purposes which emerges from stomach through an anterior gastrostomy. Now we present the satisfactory results obtained in five cases of duodenal fistulas, or surgery involving risk of suture failure, enabling patients to feed early in postoperatory. In three reoperated patients it was observed that the anastomosis closes spontaneously sorne time after the catheter is taken out.